El abandono de una casa romana en Cartagena (solar C/. Cuatro Santos, nº 40) - Vidal Nieto, Milagros; de Miquel, Luis E. (Antigüedad y Cristianismo, 1998)
We will describe and, at the same time, attempt to reconstruct the history of the site at no 40 Cuatro Santos Street. Different layers are defined and the various stages of population that can be deduced from this infomation are explained. The debate concerning the end of the Roman house is discussed, based on the materials discovered. The deductions that can be made from the discovery of these materials are discussed, as are the implications.